2019
DOI: 10.1097/md.0000000000013906
|View full text |Cite
|
Sign up to set email alerts
|

Qishenyiqi dripping pill improves ventricular remodeling and function in patients with chronic heart failure

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…(4) Brain Natriuretic Peptide (BNP) . Twenty-one pieces of literature [ 19 – 26 , 30 , 33 , 35 , 36 , 38 – 41 , 43 , 48 , 50 , 54 , 55 ] performed a meta-analysis on BNP, including 12 pieces of low-quality evidence [ 19 – 22 , 24 – 26 , 33 , 35 , 40 , 43 , 50 ], and 9 pieces of very low-quality evidence [ 23 , 30 , 36 , 38 , 39 , 41 , 48 , 54 , 55 ]. The results showed that the difference was statistically significant ( P < 0.05), suggesting that Tongxinluo Capsules, Buyi Qiangxin Tablets, and Yixinshu Capsules combined with CT may significantly reduce BNP in HF patients compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Brain Natriuretic Peptide (BNP) . Twenty-one pieces of literature [ 19 – 26 , 30 , 33 , 35 , 36 , 38 – 41 , 43 , 48 , 50 , 54 , 55 ] performed a meta-analysis on BNP, including 12 pieces of low-quality evidence [ 19 – 22 , 24 – 26 , 33 , 35 , 40 , 43 , 50 ], and 9 pieces of very low-quality evidence [ 23 , 30 , 36 , 38 , 39 , 41 , 48 , 54 , 55 ]. The results showed that the difference was statistically significant ( P < 0.05), suggesting that Tongxinluo Capsules, Buyi Qiangxin Tablets, and Yixinshu Capsules combined with CT may significantly reduce BNP in HF patients compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
“…(6) Left Ventricular Ejection Fraction (LVEF) . Thirty-two pieces of literature [ 19 – 25 , 28 – 30 , 33 , 35 – 46 , 48 – 56 ] focused on LVEF, including 6 pieces of moderate-quality evidence [ 30 , 35 , 37 , 51 – 53 ], 19 pieces of low-quality evidence [ 19 – 21 , 23 , 28 , 29 , 33 , 36 , 39 , 41 – 46 , 48 , 49 , 55 , 56 ], and 9 pieces of very low-quality evidence [ 22 , 24 , 25 , 30 , 38 , 40 , 50 , 51 , 54 ]. A meta-analysis [ 54 ] of 818 CHF patients from 8 RCTs showed that no statistically significant differences between Yangxinshi Pills are combined with CT group and CT group.…”
Section: Resultsmentioning
confidence: 99%
“…A lack of consistency across these studies used to be explained by small sample sizes and differences in treatment courses, among other factors. Only one previous meta-analysis has been published in 2019 by Chang et al [ 13 ]. It included 12 high-quality studies (Jadad ≥ 2) involving 942 patients with CHF and suggested that QSYQ is effective and safe for improving ventricular remodeling and heart function in patients, consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of these studies are not sufficient to establish standards for evidence-based practice, as most are limited by small sample sizes and differences in treatment duration. To the best of our knowledge, only one meta-analysis has evaluated the effects of QSYQ on CHF, including only 12 studies with a Jadad score of ≥2 [ 13 ]. Quality assessment is essential for meta-analyses; however, the Jadad scale is not suitable for study exclusion, as it contains no mention of allocation concealment, which is important in the evaluation of an RCT's internal validity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…QSYQDP is approved by the China State Food and Drug Administration in 2003 for the treatment of cardiovascular disease. Numerous pharmacological studies have revealed the synergistic effect of QSYQDP on cardiovascular diseases ( Chang et al, 2019 ). Recently, QSYQDP (175 mg/kg/day) ( Lu et al, 2015 ) has been shown to alleviate cardiac fibrosis by blocking the activation of RAAS and RAAS activation pathways, particularly by regulating the expression of AT1R and AT2R, and restoring the Ang II-NADPH oxidation-ROS-MMP pathway.…”
Section: Related Research On the Prevention And Treatment Of Myocardi...mentioning
confidence: 99%